A novel raiometric fluorescence probe based on silicon quantum dots and copper nanoclusters for visual assay of l-cysteine in milks. (15th June 2022) - Ma, Yange; Mei, He; Li, Yanyan; Zhou, Peipei; Mao, Guangyun; Wang, Huili; Wang, Xuedong
Highlights: SiQDs and CuNCs are integrated to construct a novel ratiometric fluorescence probe. Fluorescence of SiQDs can be prominently quenched by CuNCs through a FRET process. The probe is used to detect l -Cys in milk without mediation of intermediate chemicals. Fluorescence quenching of CuNCs by l -Cys is via PET process based on band-gap theory. This ratiometric probe offers high selectivity, recovery for assay of l -Cys in milks. Abstract: l -cysteine (l -Cys) plays an important role in many physiological processes. The previously reported methodologies for l -Cys detection have many drawbacks, and thus the development of specific/sensitive approaches is crucial for its direct/quick assay in food matrices. Herein, silicon quantum dots (SiQDs) and glutathione-stabilized copper nanoclusters (CuNCs) were successfully synthesized and integrated as a ratiometric fluorescent probe for assay l -Cys assay in milks. The fluorescence of SiQDs was quenched by CuNCs through fluorescence resonance energy-transfer process. Upon addition of l -Cys, the 440-nm fluorescence of SiQDs changed insignificantly, while the 650-nm fluorescence of CuNCs decreased significantly. Ratiometric fluorescence signal was linear in the l -Cys concentration range of 0.25 μM to 2.5 mM with a detection limit of 75 nM and visual color changes from red to blue. The probe can realize rapid and portable detection without the participation of intermediate ions, and has good selectivity and accuracy for l -cysteine in milk samples.